IMPLEMENTATION OF MANAGEMENT INFORMATION SYSTEMS IN PROMOTING SCHOOLS IN STATE JUNIOR HIGH SCHOOLS 1 LABUHANHAJI ACEH SELATAN - Feri Yuliarman; Akmaluddin; Siti Mayang Sari; Mhd. Syafii (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The school management information system implemented by Labuhanhaji 1 Public Middle School was challenged after a government program to establish several other schools in Labuhanhaji, so the school carried out promotions to attract public interest to be willing to send their children to school. This study aims to determine the planning carried out in promoting schools, the implementation of management information systems in promoting schools, the supporting factors and obstacles to implementing management information systems in promoting schools. This type of research is field research, which is descriptive qualitative. Data collection is done by observation, interviews, and documentation. The research subjects were school principals, teachers, school administrators, student affairs teachers, student council members and students. The results of the study show that in promoting schools the school makes good planning in terms of the content of the information message conveyed, the facilities and infrastructure used, the structure of the party conveying the information, the target of the information, the location and purpose. Implementation of management information systems in promoting schools is carried out in several ways, namely utilizing social media, utilizing print media and holding outreach and seminars. Factors supporting the development of information and communication technology in the form of online media, social media and so on. The obstacle to the implementation of management information systems in promoting schools is the minimal level of human resources for members, especially in the dissemination of information and the limited facilities and infrastructure that can be used in conveying information